Down-Regulating the Expression of 53 Soybean Transcription Factor Genes Uncovers a Role for SPEECHLESS in Initiating Stomatal Cell Lineages during Embryo Development. Issue 3 (11th May 2015) - Danzer, John; Mellott, Eric; Bui, Anhthu Q.; Le, Brandon H.; Martin, Patrick; Hashimoto, Meryl; Perez-Lesher, Jeanett; Chen, Min; Pelletier, Julie M.; Somers, David A.; Goldberg, Robert B.; Harada, John J.
Abstract : An RNA interference screen of 53 transcription factor mRNAs that accumulate specifically during soybean seed development identified a homolog of an epidermal factor required to initiate stomatal cell lineages during embryo development. Abstract: We used an RNA interference screen to assay the function of 53 transcription factor messenger RNAs (mRNAs) that accumulate specifically within soybean ( Glycine max ) seed regions, subregions, and tissues during development. We show that basic helix-loop-helix (bHLH ) transcription factor genes represented by Glyma04g41710 and its paralogs are required for the formation of stoma in leaves and stomatal precursor complexes in mature embryo cotyledons. Phylogenetic analysis indicates that these bHLH transcription factor genes are orthologous to Arabidopsis ( Arabidopsis thaliana ) SPEECHLESS ( SPCH ) that initiate asymmetric cell divisions in the leaf protoderm layer and establish stomatal cell lineages. Soybean SPCH ( GmSPCH ) mRNAs accumulate primarily in embryo, seedling, and leaf epidermal layers. Expression of Glyma04g41710 under the control of the SPCH promoter rescues the Arabidopsis spch mutant, indicating that Glyma04g41710 is a functional ortholog of SPCH . Developing soybean embryos do not form mature stoma, and stomatal differentiation is arrested at the guard mother cell stage. We analyzed the accumulation of GmSPCH mRNAs during soybean seed development and mRNAs orthologous to MUTE, FAMA, and INDUCER OF C-REPEAT/DEHYDRATION RESPONSIVE ELEMENT-BINDING FACTOR EXPRESSION1/SCREAM2 that are required for stoma formation in Arabidopsis. The mRNA accumulation patterns provide a potential explanation for guard mother cell dormancy in soybean embryos. Our results suggest that variation in the timing of bHLH transcription factor gene expression can explain the diversity of stomatal forms observed during plant development.